Stray dogs, Journey to the West 2 films - Lee, Kang-Sheng 1968-; Yang, Kuei Mei 1959-; Lu, Yijing 1958- (New Wave Films, 2015)
STRAY DOGS (Jiaoyou)The latest film by visionary director Tsai Ming-liang (Goodbye Dragon Inn) links together a series of sumptuously composed scenes that tell the story of a broken family living on the margins of Taipei society through tableau-like scenes, often without words. ĐLike Tsai's sublime I Don't Want to Sleep Alone, Stray Dogs plucks its characters from society's margins; without sentimentalizing their subjects, these films exude empathy for day labourers and the homeless. As one mysterious, gorgeously composed scene gives way to the next, we come to know these characters, and something of their history, a time when they indeed had a home, a mother, a very different sort of life. We gaze into their past with them, are invited to share in their loss, and, gradually, imagine some brighter future.ĐJOURNEY TO THE WEST (Xi You)Loosely based on the life of Xuanzang, a seventh-century Buddhist monk who trekked across Asia for 17 years in search of Đthe voidĐ, Journey to the West provides, with its unusual, brilliantly chosen camera angles a collage of various districts in Marseille, creating a hypnotic space in which this meditative peregrination becomes a surprising journey of discovery. (Toronto Film Festival Catalogue)
Orig.: RC/F 2013 ; F/RC 2014
Keywords: Film